Paper grinding roller repaired by high-entropy alloy material and ultrahigh-speed laser cladding method

By using CoCrFeNiMo high-entropy alloy material on the surface of the paper rolling roller for ultra-high-speed laser cladding technology, the problem of insufficient surface strength and wear resistance of the paper rolling roller in the prior art has been solved, and the wear resistance and corrosion resistance of the paper rolling roller are improved, reducing the repair cost.

CN119615153APending Publication Date: 2025-03-14HEBEI JINGJINJI REMANUFACTURING IND TECH RES CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411921565.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art has limitations in improving the surface strength and wear resistance of paper rolling rollers. Plasma cladding technology leads to deformation of repair workpieces, supersonic flame spraying lacks coating bonding, and high repair costs.

Method used

CoCrFeNiMo high-entropy alloy material is used to form a cladding layer on the surface of the paper rolling roller through ultra-high-speed laser cladding technology, achieving uniform integration between the high-entropy alloy powder and the surface matrix of the paper rolling roller, enhancing the wear resistance and corrosion resistance of the paper rolling roller.

Benefits of technology

It effectively improves the wear resistance and service life of the paper rolling roller, reduces the repair cost, and the coating has good bonding and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005208147510000171
    Figure BDA0005208147510000171
  • Figure HDA0005208147520000011
    Figure HDA0005208147520000011
  • Figure HDA0005208147520000012
    Figure HDA0005208147520000012
Patent Text Reader

Abstract

The invention provides an application of a CoCrFeNiMo high-entropy alloy in the aspect of repairing a paper grinding roller and / or a coating of the paper grinding roller. The CoCrFeNiMo high-entropy alloy is prepared from the following elements in percentage by mass: 20.81 percent to 22.81 percent of Co, 17.51 percent to 19.51 percent of Cr, 20.01 percent to 23.01 percent of Fe, 18.90 percent to 21.90 percent of Ni and 12.76 percent to 15.76 percent of Mo. The invention further provides a high-entropy alloy cladding material and an ultra-high-speed laser cladding method, the easily damaged part of the paper grinding roller can be strengthened or efficiently repaired, the wear resistance of the surface of the paper grinding roller can be effectively improved, and therefore the use reliability and the production efficiency of the paper grinding roller are improved. And the ultrahigh-speed laser cladding method adopted by the invention has the characteristics of high powder utilization rate and easiness in controlling the thickness of a cladding layer, and the repair cost of the paper grinding roller can be remarkably reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of surface modification and coating preparation of paper mill rollers, and relates to the application of CoCrFeNiMo high entropy alloy in repairing paper mill rollers and / or paper mill roller coatings, a paper mill roller or a repaired paper mill roller, a preparation method or a repair method of a paper mill roller, and in particular, to a paper mill roller repaired with a high entropy alloy material and an ultra-high-speed laser cladding method. Background Art

[0002] The paper roller is an important part in the papermaking and printing industry. The main function of the paper roller is to transfer paper. As the speed of the printing press is getting higher and higher, smooth paper transfer and no paper jams have become one of the bottlenecks for speeding up. The performance of the paper roller directly affects the yield and production efficiency of papermaking and printing products. The base material of the paper roller is 42CrMo steel, which cannot provide it with high hardness and high wear resistance. At the same time, the paper roller has the disadvantage of low service life. In order to improve the wear resistance and friction of the paper roller and ensure the smoothness of paper transfer, preparing a wear-resistant coating on the surface of the paper roller is an effective solution.

[0003] In order to solve the problem of low surface strength of paper rolling rollers, the commonly used technical solutions are: using plasma cladding technology to process Ni+WC cladding layer on the surface of paper rolling rollers, using supersonic flame spraying technology to process WC coating on the surface of paper rolling rollers, etc. These surface engineering technologies are used to enhance the performance of the surface of paper rolling rollers. However, due to the large heat input of plasma cladding technology, it is easy to cause deformation of repaired workpieces (especially small parts), which is not conducive to the mechanical processing of paper rolling rollers after repair. At the same time, the rough surface of plasma cladding coating will also increase the cost of mechanical processing after the repair of paper rolling rollers. The combination of the coating prepared by supersonic flame spraying and the surface of the repaired part substrate is a mechanical fit. Therefore, the bonding strength of the coating prepared by thermal spraying cannot fully meet the requirements of the working conditions of the paper rolling roller, and it is easy to cause problems such as local shedding of the coating, which in turn affects the printing quality. In addition, the spraying process also has the problem of low utilization rate of repair materials, which leads to excessively high repair costs.

[0004] Therefore, how to find a more suitable way to improve the surface strength performance of the paper rolling roller, solve the above-mentioned problems existing in the existing technical solutions, and realize the remanufacturing of the paper rolling roller efficiently and at low cost is a technical problem that needs to be urgently solved in the papermaking and printing industry, and it is also one of the problems that many front-line researchers in the industry need to solve urgently. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide an application of CoCrFeNiMo high entropy alloy in repairing a paper milling roller and / or a paper milling roller coating, a paper milling roller or a repaired paper milling roller, a preparation method or a repair method of a paper milling roller, and in particular, a paper milling roller repaired with a high entropy alloy material. The present invention utilizes ultra-high-speed laser cladding technology to achieve uniform metallurgical integration of high entropy alloy powder and the surface matrix of the paper milling roller, so that the size of the easily damaged part of the paper milling roller is repaired while the performance is further enhanced, effectively extending the service life of the paper milling roller.

[0006] The present invention provides an application of CoCrFeNiMo high entropy alloy in repairing a paper rolling roller and / or a paper rolling roller coating;

[0007] The CoCrFeNiMo high entropy alloy, measured by element mass content, comprises:

[0008] Co: 20.81% to 22.81%, Cr: 17.51% to 19.51%, Fe: 20.01% to 23.01%, Ni: 18.90% to 21.90% and Mo: 12.76% to 15.76%.

[0009] Preferably, the application method includes applying by ultra-high-speed laser cladding method;

[0010] The CoCrFeNiMo high entropy alloy is specifically CoCrFeNiMo spherical powder;

[0011] The material of the paper rolling roller includes CrMo steel.

[0012] Preferably, the CoCrFeNiMo spherical powder is obtained by spray granulation of CoCrFeNiMo slurry including CoCrFeNiMo high entropy alloy powder, a dispersion medium and a binder;

[0013] The particle size of the CoCrFeNiMo spherical powder is 30 to 50 μm;

[0014] The applications include improving the wear resistance and / or corrosion resistance of paper mill rollers.

[0015] Preferably, the thickness of the coating is 0.2 to 1 mm;

[0016] In the CoCrFeNiMo slurry, the content of the binder is 0.6wt% to 0.8wt%;

[0017] In the CoCrFeNiMo slurry, the content of the dispersion medium is 49.2wt% to 49.4wt%.

[0018] The present invention provides a paper milling roller or a repaired paper milling roller, comprising a paper milling roller and a coating compounded on the paper milling roller;

[0019] The coating is a CoCrFeNiMo high entropy alloy coating;

[0020] The CoCrFeNiMo high entropy alloy, measured by element mass content, comprises:

[0021] Co: 20.81% to 22.81%, Cr: 17.51% to 19.51%, Fe: 20.01% to 23.01%, Ni: 18.90% to 21.90% and Mo: 12.76% to 15.76%.

[0022] The present invention provides a method for preparing or repairing a paper milling roller, comprising the following steps:

[0023] 1) mixing CoCrFeNiMo high entropy alloy powder, a dispersion medium and a binder to obtain a CoCrFeNiMo slurry;

[0024] The CoCrFeNiMo high entropy alloy, measured by element mass content, comprises:

[0025] Co: 20.81% to 22.81%, Cr: 17.51% to 19.51%, Fe: 20.01% to 23.01%, Ni: 18.90% to 21.90% and Mo: 12.76% to 15.76%;

[0026] 2) The CoCrFeNiMo slurry obtained in the above step is subjected to spray granulation and sintering to obtain CoCrFeNiMo spherical powder;

[0027] 3) Under a protective atmosphere, the CoCrFeNiMo spherical powder obtained in the above steps is subjected to an ultra-high-speed laser cladding process to form a cladding layer on the to-be-repaired part of the paper rolling roller or on the paper rolling roller to be repaired, and then cooled to obtain a paper rolling roller composited with a CoCrFeNiMo high-entropy alloy coating or a repaired paper rolling roller composited with a CoCrFeNiMo high-entropy alloy coating.

[0028] Preferably, the particle size of the CoCrFeNiMo high entropy alloy powder is 45 to 100 μm;

[0029] The dispersion medium includes water;

[0030] The binder includes polyethylene;

[0031] In the CoCrFeNiMo slurry, the content of the binder is 0.6wt% to 0.8wt%;

[0032] In the CoCrFeNiMo slurry, the content of the dispersion medium is 49.2wt% to 49.4wt%;

[0033] The solid content of the CoCrFeNiMo slurry is 50% to 65%.

[0034] Preferably, the mixing method includes grinding and mixing;

[0035] The air inlet temperature of the spray granulation is 280-320°C;

[0036] The outlet temperature of the spray granulation is 70-90°C;

[0037] The sintering temperature is 800-1100°C;

[0038] The particle size of the CoCrFeNiMo spherical powder is 30-50 μm.

[0039] Preferably, the ultra-high-speed laser cladding process is specifically to perform ultra-high-speed laser cladding by coaxial powder feeding;

[0040] The laser power of the ultra-high-speed laser cladding process is 3500-3700W;

[0041] The spot diameter of the ultra-high-speed laser cladding process is 2 to 3 mm;

[0042] The powder feeding rate of the ultra-high-speed laser cladding process is 34-45 g / min.

[0043] Preferably, the scanning speed of the ultra-high-speed laser cladding process is 20 to 30 m / min;

[0044] The overlap rate of the ultra-high-speed laser cladding process is 70% to 85%;

[0045] The shielding gas flow rate of the ultra-high-speed laser cladding process is 9 to 14 L / min;

[0046] The cooling step also includes a machining step;

[0047] The CoCrFeNiMo high entropy alloy coating includes a CoCrFeNiMo high entropy alloy coating with a textured structure.

[0048] The present invention provides an application of CoCrFeNiMo high entropy alloy in repairing a paper milling roller and / or a paper milling roller coating; the CoCrFeNiMo high entropy alloy comprises, by element mass content, Co: 20.81% to 22.81%, Cr: 17.51% to 19.51%, Fe: 20.01% to 23.01%, Ni: 18.90% to 21.90% and Mo: 12.76% to 15.76%. Compared with the prior art, the present invention believes that high entropy alloy is a new type of alloy material that has attracted much attention in recent years, and has excellent high-temperature wear resistance, corrosion resistance and oxidation resistance. However, the crystal structure of the high entropy alloy is mainly composed of a face-centered cubic crystal structure (FCC) phase and a body-centered cubic crystal structure (BCC) phase. The (FCC) phase has excellent plasticity, but low yield strength, while the (BCC) phase has high yield strength and poor plasticity.

[0049] Based on this, the present invention creatively designs a specific CoCrFeNiMo high entropy alloy for coating the surface of a paper milling roller, and it is more capable of being used for repairing paper milling rollers. The main function of using the CoCrFeNiMo high entropy alloy cladding layer is to enhance the wear resistance of the paper milling roller. Moreover, the improved elemental composition of the CoCrFeNiMo high entropy alloy designed by the present invention makes it more conducive to the laser cladding process in terms of physical and chemical properties. This is due to the multi-dimensionality of the CoCrFeNiMo high entropy alloy, which gives it a "diffusion benefit". More active atoms are more likely to diffuse into vacancies, achieving the effect of enhancing the performance of the coating. The addition of the Mo element promotes the "crystal distortion effect" of the coating, which is conducive to the formation of the (BCC) phase. This is because the atomic size of the Mo element is large, the bond type and lattice potential energy are also different, and the crystal structure of the coating is easily distorted, so that the CoCrFeNiMo high entropy alloy coating has extremely high hardness, good wear resistance and corrosion resistance, and can significantly improve the comprehensive performance of the functional layer after the repair of the paper milling roller.

[0050] The present invention also provides a method for preparing or repairing a paper rolling roller by ultra-high-speed laser cladding. The laser has the characteristics of high directionality, high monochromaticity, high coherence and high energy density. The ultra-high-speed laser cladding technology is used as the surface engineering processing technology of the paper rolling roller. Compared with the conventional cladding process, it has the characteristics of small heat input, high efficiency and strong bonding force of the cladding layer. It is more suitable for the preparation of surface strengthening coatings for small precision parts and complex parts such as paper rolling rollers.

[0051] The high entropy alloy cladding material and ultra-high speed laser cladding method provided by the present invention can realize the strengthening or efficient repair of the easily damaged parts of the paper rolling roller, and can effectively improve the wear resistance of the surface of the paper rolling roller, thereby improving the reliability and production efficiency of the paper rolling roller; the cladding layer prepared by the present invention can provide good wear resistance, and due to the introduction of Ni and Mo elements, it can also give the cladding layer excellent corrosion resistance, which can significantly reduce the corrosion and wear effect of ink on the paper rolling roller. Moreover, the ultra-high speed laser cladding method adopted by the present invention has the characteristics of high powder utilization rate and easy control of cladding layer thickness, which can significantly reduce the repair cost of the paper rolling roller. The high entropy alloy cladding material and ultra-high speed laser cladding method provided by the present invention are suitable for the strengthening of new products of the working layer of the paper rolling roller, and are also suitable for the remanufacturing of failed paper rolling rollers, thereby realizing the recycling of waste paper rolling rollers, reducing resource waste, and significantly reducing product production costs; the material system designed by the present invention and related application scenarios have good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is a morphology image of the CoCrFeNiMo high entropy alloy cladding powder prepared by the present invention;

[0053] Figure 2 EDS of CoCrFeNiMo high entropy alloy cladding powder prepared by the present invention;

[0054] Figure 3 The cross-sectional morphology of the coating prepared in Comparative Example 1 and Example 1 of the present invention. Figure 3 In the figure, 1 is the cross-sectional morphology of the coating prepared in comparative example 1, and 2 is the cross-sectional morphology of the coating prepared in example 1.

[0055] Figure 4 This is a real picture of the preparation of the wear-resistant layer of the paper milling roller prepared by the present invention. Figure 4 In the figure, 1 is the pre-treatment of the paper rolling roller, 2 is the coating cladding of the paper rolling roller, and 3 is the post-processing of the paper rolling roller. DETAILED DESCRIPTION

[0056] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0057] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0058] The raw materials used in the present invention have no particular limitation on their purity. The present invention preferably uses industrial purity or conventional purity in the field of paper roller coating.

[0059] The brands and abbreviations of all raw materials of the present invention are conventional brands and abbreviations in the art. Each brand and abbreviation is clear and definite in the field of its related use. Those skilled in the art can purchase them from the market or prepare them by conventional methods according to the brands, abbreviations and corresponding uses.

[0060] The abbreviations of all processes of the present invention are conventional abbreviations in the field, and each abbreviation is clear and unambiguous in the field of its related use. Those skilled in the art can understand its conventional process steps based on the abbreviations.

[0061] The present invention provides an application of CoCrFeNiMo high entropy alloy in repairing a paper rolling roller and / or a paper rolling roller coating;

[0062] The CoCrFeNiMo high entropy alloy, measured by element mass content, comprises:

[0063] Co: 20.81% to 22.81%, Cr: 17.51% to 19.51%, Fe: 20.01% to 23.01%, Ni: 18.90% to 21.90% and Mo: 12.76% to 15.76%.

[0064] In the present invention, the Co content is 20.81% to 22.81%, may be 21% to 22%, may be 21.5% to 21.81%, and may be specifically 21.81%.

[0065] In the present invention, the Cr content is 17.51% to 19.51%, may be 18% to 19.51%, may be 18.5% to 19.51%, and may be specifically 19.51%.

[0066] In the present invention, the content of Fe is 20.01% to 23.01%, may be 21.01% to 23.01%, may be 21.01% to 22.01%, and specifically may be 21.01%.

[0067] In the present invention, the Ni content is 18.90% to 21.90%, may be 19.90% to 21.90%, may be 20.90% to 21.90%, and specifically may be 21.90%.

[0068] In the present invention, the content of Mo is 12.76% to 15.76%, may be 13.76% to 15.76%, may be 14.76% to 15.76%, and may be specifically 15.76%.

[0069] In the present invention, the application method preferably includes application by ultra-high-speed laser cladding method.

[0070] In the present invention, the CoCrFeNiMo high entropy alloy is preferably CoCrFeNiMo spherical powder.

[0071] In the present invention, the material of the paper rolling roller preferably includes CrMo steel.

[0072] In the present invention, the CoCrFeNiMo spherical powder is preferably obtained by spray granulation of CoCrFeNiMo slurry comprising CoCrFeNiMo high entropy alloy powder, a dispersion medium and a binder.

[0073] In the present invention, the particle size of the CoCrFeNiMo spherical powder is preferably 30 to 50 μm, more preferably 34 to 46 μm, and more preferably 38 to 42 μm.

[0074] In the present invention, the application preferably includes the application of improving the wear resistance and / or corrosion resistance of the paper milling roller, and more preferably the application of improving the wear resistance or corrosion resistance of the paper milling roller.

[0075] In the present invention, the thickness of the coating is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, more preferably 0.4 to 0.8 mm, and more preferably 0.5 to 0.7 mm.

[0076] In the present invention, in the CoCrFeNiMo slurry, the content of the binder is preferably 0.6wt% to 0.8wt%, more preferably 0.64wt% to 0.76wt%, and more preferably 0.68wt% to 0.72wt%.

[0077] In the present invention, in the CoCrFeNiMo slurry, the content of the dispersion medium is preferably 49.2wt% to 49.4wt%, more preferably 49.24wt% to 49.36wt%, and more preferably 49.28wt% to 49.32wt%.

[0078] The present invention provides a paper milling roller or a repaired paper milling roller, comprising a paper milling roller and a coating compounded on the paper milling roller;

[0079] The coating is a CoCrFeNiMo high entropy alloy coating;

[0080] The CoCrFeNiMo high entropy alloy, measured by element mass content, comprises:

[0081] Co: 20.81% to 22.81%, Cr: 17.51% to 19.51%, Fe: 20.01% to 23.01%, Ni: 18.90% to 21.90% and Mo: 12.76% to 15.76%.

[0082] In the present invention, the content of Co is 20.81% to 22.81%, may be 21% to 22%, or may be 21.5% to 21.81%.

[0083] In the present invention, the Cr content is 17.51% to 19.51%, may be 18% to 19.51%, or may be 18.5% to 19.51%.

[0084] In the present invention, the content of Fe is 20.01% to 23.01%, may be 21.01% to 23.01%, or may be 21.01% to 22.01%.

[0085] In the present invention, the Ni content is 18.90% to 21.90%, may be 19.90% to 21.90%, or may be 20.90% to 21.90%.

[0086] In the present invention, the content of Mo is 12.76% to 15.76%, may be 13.76% to 15.76%, or may be 14.76% to 15.76%.

[0087] The present invention provides a method for preparing or repairing a paper milling roller, comprising the following steps:

[0088] 1) mixing CoCrFeNiMo high entropy alloy powder, a dispersion medium and a binder to obtain a CoCrFeNiMo slurry;

[0089] The CoCrFeNiMo high entropy alloy, measured by element mass content, comprises:

[0090] Co: 20.81% to 22.81%, Cr: 17.51% to 19.51%, Fe: 20.01% to 23.01%, Ni: 18.90% to 21.90% and Mo: 12.76% to 15.76%;

[0091] 2) The CoCrFeNiMo slurry obtained in the above step is subjected to spray granulation and sintering to obtain CoCrFeNiMo spherical powder;

[0092] 3) Under a protective atmosphere, the CoCrFeNiMo spherical powder obtained in the above steps is subjected to an ultra-high-speed laser cladding process to form a cladding layer on the to-be-repaired part of the paper rolling roller or on the paper rolling roller to be repaired, and then cooled to obtain a paper rolling roller composited with a CoCrFeNiMo high-entropy alloy coating or a repaired paper rolling roller composited with a CoCrFeNiMo high-entropy alloy coating.

[0093] The present invention firstly mixes CoCrFeNiMo high entropy alloy powder, a dispersion medium and a binder to obtain CoCrFeNiMo slurry;

[0094] The CoCrFeNiMo high entropy alloy, measured by element mass content, comprises:

[0095] Co: 20.81% to 22.81%, Cr: 17.51% to 19.51%, Fe: 20.01% to 23.01%, Ni: 18.90% to 21.90% and Mo: 12.76% to 15.76%.

[0096] In the present invention, the content of Co is 20.81% to 22.81%, may be 21% to 22%, or may be 21.5% to 21.81%.

[0097] In the present invention, the Cr content is 17.51% to 19.51%, may be 18% to 19.51%, or may be 18.5% to 19.51%.

[0098] In the present invention, the content of Fe is 20.01% to 23.01%, may be 21.01% to 23.01%, or may be 21.01% to 22.01%.

[0099] In the present invention, the Ni content is 18.90% to 21.90%, may be 19.90% to 21.90%, or may be 20.90% to 21.90%.

[0100] In the present invention, the content of Mo is 12.76% to 15.76%, may be 13.76% to 15.76%, or may be 14.76% to 15.76%.

[0101] In the present invention, the particle size of the CoCrFeNiMo high entropy alloy powder is preferably 45 to 100 μm, more preferably 55 to 90 μm, and more preferably 65 to 80 μm.

[0102] In the present invention, the dispersion medium preferably includes water.

[0103] In the present invention, the binder preferably includes polyethylene.

[0104] In the present invention, the content of the binder in the CoCrFeNiMo slurry is preferably 0.6wt% to 0.8wt%, more preferably 0.64wt% to 0.76wt%, and more preferably 0.68wt% to 0.72wt%.

[0105] In the present invention, in the CoCrFeNiMo slurry, the content of the dispersion medium is preferably 49.2wt% to 49.4wt%, more preferably 49.24wt% to 49.36wt%, and more preferably 49.28wt% to 49.32wt%.

[0106] In the present invention, the solid content of the CoCrFeNiMo slurry is preferably 50% to 65%, more preferably 50% to 60%, more preferably 50% to 55%, and specifically 50%.

[0107] In the present invention, the mixing method preferably includes grinding mixing. Specifically, the mixing time is preferably greater than or equal to 4 hours.

[0108] In the present invention, the CoCrFeNiMo slurry obtained in the above steps is subjected to spray granulation and sintering to obtain CoCrFeNiMo spherical powder.

[0109] In the present invention, the air inlet temperature of the spray granulation is preferably 280-320°C, more preferably 285-315°C, more preferably 290-310°C, more preferably 295-325°C.

[0110] In the present invention, the outlet temperature of the spray granulation is preferably 70-90°C, more preferably 74-86°C, and more preferably 78-82°C.

[0111] In the present invention, the sintering temperature is preferably 800-1100°C, more preferably 850-1050°C, and even more preferably 900-1000°C.

[0112] In the present invention, the particle size of the CoCrFeNiMo spherical powder is preferably 30 to 50 μm, more preferably 34 to 46 μm, and more preferably 38 to 42 μm.

[0113] Finally, in the present invention, the CoCrFeNiMo spherical powder obtained in the above steps is subjected to an ultra-high-speed laser cladding process under a protective atmosphere to form a cladding layer on the to-be-repaired part of the paper rolling roller or on the paper rolling roller to be repaired, and then cooled to obtain a paper rolling roller composited with a CoCrFeNiMo high-entropy alloy coating or a repaired paper rolling roller composited with a CoCrFeNiMo high-entropy alloy coating.

[0114] In the present invention, the ultra-high speed laser cladding process is preferably performed by using a coaxial powder feeding method to perform ultra-high speed laser cladding;

[0115] In the present invention, the laser power of the ultra-high-speed laser cladding process is preferably 3500-3700W, more preferably 3550-3700W, more preferably 3600-3700W, and specifically may be 3700W.

[0116] In the present invention, the spot diameter of the ultra-high-speed laser cladding process is preferably 2-3 mm, more preferably 2.4-3 mm, more preferably 2.8-3 mm, and specifically may be 3 mm.

[0117] In the present invention, the powder feeding rate of the ultra-high speed laser cladding process is preferably 34-45 g / min, more preferably 37-42 g / min, more preferably 40-42 g / min, and specifically may be 42 g / min.

[0118] In the present invention, the scanning speed of the ultra-high speed laser cladding process is preferably 20-30 m / min, more preferably 22-28 m / min, more preferably 25-26 m / min, and specifically 25 m / min.

[0119] In the present invention, the overlap rate of the ultra-high speed laser cladding process is preferably 70% to 85%, more preferably 72% to 83%, and more preferably 75% to 80%. Specifically, it can be 75%.

[0120] In the present invention, the shielding gas flow rate of the ultra-high-speed laser cladding process is preferably 9-14 L / min, more preferably 9-12 L / min, more preferably 9-10 L / min, and specifically may be 9 L / min.

[0121] In the present invention, the cooling step preferably further includes a machining step.

[0122] In the present invention, the CoCrFeNiMo high entropy alloy coating preferably includes a CoCrFeNiMo high entropy alloy coating having a textured structure.

[0123] The present invention provides a high entropy alloy material and an ultra-high speed laser cladding method for repairing a paper rolling roller. The present invention utilizes ultra-high speed laser cladding technology to achieve uniform metallurgical integration of high entropy alloy powder and the surface matrix of the paper rolling roller, so that the size of the easily damaged parts of the paper rolling roller is repaired while the performance is further enhanced, effectively extending the service life of the paper rolling roller.

[0124] The present invention is a complete and detailed overall technical solution, which better ensures the structure and composition of the CoCrFeNiMo high entropy alloy coating, further improves the repair effect of the paper milling roller and the surface wear resistance of the paper milling roller, and the application of the above-mentioned CoCrFeNiMo high entropy alloy in repairing the paper milling roller and / or the paper milling roller coating, a paper milling roller or a repaired paper milling roller, and a preparation method or repair method of a paper milling roller can specifically include the following contents:

[0125] The specific scheme of the present invention comprises the following steps:

[0126] a. Prefabrication and preparation of high entropy alloy powder;

[0127] (1) using a laboratory balance to weigh a corresponding mass of CoCrFeNiMo high entropy alloy powder, the composition of which is as follows: Co: 20.81% to 22.81%, Cr: 17.51% to 19.51%, Fe: 20.01% to 23.01%, Ni: 18.90% to 21.90% and Mo: 12.76% to 15.76%;

[0128] (2) using deionized water as a dispersion medium, adding weighed powder, and using polyvinyl alcohol (PVA) as a binder to prepare a CoCrFeNiMo slurry, wherein the binder content is 0.6wt% to 0.8wt%, the dispersion medium content is 49.2wt% to 49.4wt%, and the slurry solid content is 50%; the slurry is mixed uniformly with a planetary ball mill at a ball-to-material ratio of 1:1, and the mixing time is not less than 4 hours;

[0129] (3) The mixed slurry is sprayed and granulated by a centrifugal spray drying device, wherein the air inlet temperature is controlled at 280-320°C, the air outlet temperature is controlled at 70-90°C, and the atomizer rotation frequency is controlled at about 35 Hz; the granulated powder is sintered at 800-1100°C for 4 hours to remove the binder, and the sintered powder is screened for particle size to obtain 30-50 μm CoCrFeNiMo spherical powder suitable for laser cladding;

[0130] (4) The screened material is placed in a constant temperature drying oven set at a preset temperature of 130°C for drying until use.

[0131] b. Pre-treat the key parts of the paper rolling roller;

[0132] The paper roller to be repaired is pre-treated, and the failure and oxidation layers of the part to be repaired are removed by lathe, and then the rust, oil stains and impurities of the part to be repaired are removed. Among them, the rust can be removed by chemical cleaning with weak acid solution, and the oil stains can be removed by wiping with alcohol. Finally, the treated paper roller is clamped on the bed with a clamp.

[0133] c. Ultra-high-speed laser cladding technology was used to repair the key surface of the paper roller by coaxial powder feeding. The specific cladding process parameters were: laser power of 3700W, spot diameter of 3mm, powder feeding rate of 42g / min, scanning speed of 25m / min, overlap rate of 75%, cladding layer thickness of 1mm, and protective gas flow rate of 9L / min. In the cladding process, the laser cladding area was protected by inert gas.

[0134] d. Post-processing: The paper milling roller repaired in step c is subjected to mechanical post-processing. The specific steps are as follows:

[0135] (1) Allow the clad paper roller to cool to room temperature, then grind it to the required size on the drawing.

[0136] (2) Processing mesh patterns on the coating surface, with a transverse angle of 45°, to increase the longitudinal friction of the paper rolling roller surface, meeting the assembly and use requirements of the paper rolling roller.

[0137] (3) Finally, make correction for the runout. The runout of the paper rolling roller should not exceed 0.02A.

[0138] Specifically, the thickness of the cladding layer in step c is 0.2 to 1 mm.

[0139] Specifically, the inert gas in the above step c is argon.

[0140] The above content of the present invention provides the application of CoCrFeNiMo high entropy alloy in repairing paper mill rollers and / or paper mill roller coatings, a paper mill roller coated with a high entropy alloy material or a paper mill roller repaired with a high entropy alloy material, and an ultra-high-speed laser cladding method for preparing or repairing a paper mill roller. The present invention designs a specific CoCrFeNiMo high entropy alloy for coating the surface of a paper mill roller, and is more capable of being used for repairing a paper mill roller. The main function of using the CoCrFeNiMo high entropy alloy cladding layer is to enhance the wear resistance of the paper mill roller. Moreover, the improved elemental composition of the CoCrFeNiMo high entropy alloy designed by the present invention makes it more conducive to the laser cladding process in terms of physical and chemical properties. This is due to the diversity of the CoCrFeNiMo high entropy alloy, which gives it a "diffusion benefit". Atoms with stronger activity are more likely to diffuse into vacancies, thereby achieving the effect of enhancing the performance of the coating. The addition of the Mo element promotes the "crystal distortion effect" of the coating, which is conducive to the formation of the (BCC) phase. This is because the atomic size of the Mo element is large, the bond type and lattice potential energy are also different, and the crystal structure of the coating is easily distorted, which makes the CoCrFeNiMo high-entropy alloy coating have extremely high hardness, good wear resistance and corrosion resistance, and can significantly improve the comprehensive performance of the functional layer after the paper roller is repaired.

[0141] The present invention also provides a method for preparing or repairing a paper rolling roller by ultra-high-speed laser cladding. The laser has the characteristics of high directionality, high monochromaticity, high coherence and high energy density. The ultra-high-speed laser cladding technology is used as the surface engineering processing technology of the paper rolling roller. Compared with the conventional cladding process, it has the characteristics of small heat input, high efficiency and strong bonding force of the cladding layer. It is more suitable for the preparation of surface strengthening coatings for small precision parts and complex parts such as paper rolling rollers.

[0142] The high entropy alloy cladding material and ultra-high speed laser cladding method provided by the present invention can realize the strengthening or efficient repair of the easily damaged parts of the paper rolling roller, and can effectively improve the wear resistance of the surface of the paper rolling roller, thereby improving the reliability and production efficiency of the paper rolling roller; the cladding layer prepared by the present invention can provide good wear resistance, and due to the introduction of Ni and Mo elements, it can also give the cladding layer excellent corrosion resistance, which can significantly reduce the corrosion and wear effect of ink on the paper rolling roller. Moreover, the ultra-high speed laser cladding method adopted by the present invention has the characteristics of high powder utilization rate and easy control of cladding layer thickness, which can significantly reduce the repair cost of the paper rolling roller. The high entropy alloy cladding material and ultra-high speed laser cladding method provided by the present invention are suitable for the strengthening of new products of the working layer of the paper rolling roller, and are also suitable for the remanufacturing of failed paper rolling rollers, thereby realizing the recycling of waste paper rolling rollers, reducing resource waste, and significantly reducing product production costs; the material system designed by the present invention and related application scenarios have good industrial application prospects.

[0143] To further illustrate the present invention, the following detailed description is made of the application of the CoCrFeNiMo high entropy alloy coating provided by the present invention in repairing paper mill rollers and / or paper mill roller coatings, a CoCrFeNiMo high entropy alloy coating for paper mill rollers, and a paper mill roller or a repaired paper mill roller in combination with the embodiments. However, it should be understood that these embodiments are implemented on the premise of the technical scheme of the present invention, and detailed implementation methods and specific operating procedures are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention, and the protection scope of the present invention is not limited to the embodiments described below.

[0144] Comparative Example 1

[0145] CoCrFeNi high entropy alloy powder was used as a coating on the paper rolling roller substrate 42CrMo steel for comparison and to verify its performance improvement effect.

[0146] A 100mm×100mm×10mm 42CrMo steel plate was selected as the substrate, and a cladding layer was prepared on its surface. The cladding layer material was made of self-made CoCrFeNi high entropy alloy powder with a powder particle size of 45 to 100μm. All single powder raw materials were produced by "Hebei Guifa Alloy Wear-resistant Materials Co., Ltd." and the powder particle size was 2 to 25μm. The cladding process was ultra-high-speed laser cladding, and the cladding layer thickness was 0.5mm. Proceed as follows:

[0147] Step 1: Preparation of high entropy alloy powder:

[0148] (1) Use a laboratory balance to weigh the corresponding mass of CoCrFeNi high entropy alloy powder, whose composition is as follows: Co (25.32%), Cr (24.92%), Fe (25.49%), and Ni (24.26%).

[0149] (2) Deionized water was used as a dispersant, weighed powder was added, and polyvinyl alcohol (PVA) was used as a binder to prepare a CoCrFeNi slurry, wherein the binder content was 0.6wt%-0.8wt%, the dispersant content was 49.2wt%-49.4wt%, and the solid content was 50%; the slurry was mixed in a planetary ball mill with a ball-to-material ratio of 1:1 for 4 hours;

[0150] (3) CoCrFeNi spherical powder material suitable for laser cladding is prepared by spray drying, with an air inlet temperature of 280-320°C, an air outlet temperature of 70-90°C, and an atomizer rotation frequency of 35Hz; the granulated powder is sintered at 300-400°C for 4 hours to remove the binder to obtain laser cladding powder, with a sphericity of ≥85%; the above materials are placed in a constant temperature drying oven at a preset temperature of 130°C and dried for 3 hours;

[0151] Step 2: Pretreatment of substrate and cladding powder:

[0152] (1) Use sandpaper to polish the surface of the 42Cr substrate to remove surface rust. Use alcohol to wipe off the oil stains on the surface of the substrate.

[0153] (2) To ensure uniform powder particle size, use a 180-mesh powder sifter to sieve enough cladding powder. Then place the powder in a vacuum drying oven and dry it at 120°C for 2 hours. Then add the laser cladding powder into the barrel of the coaxial powder feeding laser cladding equipment.

[0154] Step 3: Preparation of cladding layer: The cladding layer was prepared by ultra-high-speed laser cladding equipment, and the parameters were: laser power of 3700 W, spot diameter of 3 mm, powder feeding rate of 42 g / min, scanning speed of 25 m / min, overlap rate of 75%, and finally a wear-resistant CoCrFeNi cladding sample with a cladding thickness of 0.5 mm was obtained;

[0155] Step 4: Post-treatment of the cladding layer: Use 1000-grit sandpaper to grind the coating surface. After treatment, the coating surface roughness Ra is 10 to 30 μm.

[0156] Example 1

[0157] The coating was prepared by using the high entropy alloy material of the present invention, and compared with the coating prepared in comparative example 1 and the paper milling roller substrate material 42CrMo steel to verify its performance improvement effect.

[0158] A 100mm×100mm×10mm 42CrMo steel plate was selected as the substrate, and a cladding layer was prepared on its surface. The cladding layer material was made of homemade CoCrFeNiMo high entropy alloy powder with a particle size of 45 to 100μm. All single powder raw materials were produced by "Hebei Guifa Alloy Wear-Resistant Materials Co., Ltd." with a powder particle size of 2 to 25μm. The cladding process was ultra-high-speed laser cladding, and the cladding layer thickness was 1mm. Proceed as follows:

[0159] Step 1: Preparation of high entropy alloy powder:

[0160] The same as step 1 of implementation 1, except that the composition of the high entropy alloy powder is changed, and the Mo component is added, and the composition ratio is as follows: Co (21.81%), Cr (19.52%), Fe (21.01%), Ni (21.90%), Mo (15.76%);

[0161] Step 2: Pretreatment of substrate and cladding powder:

[0162] Same as step 2 of comparative example 1;

[0163] Step 3: Cladding layer preparation:

[0164] Same as step 3 of comparative example 1;

[0165] Step 4: Post-treatment of cladding layer:

[0166] Same as step 4 of comparative example 1.

[0167] Example 2

[0168] A method for repairing a paper rolling roller is provided, and the specific steps are as follows:

[0169] Step 1: Preparation and pretreatment of CoCrFeNiMo high entropy alloy powder:

[0170] Powder preparation: same as Example 1;

[0171] Powder pretreatment: Use a 180-mesh powder sifter to sift a sufficient amount of cladding powder. Then place the powder in a vacuum drying oven and dry it at 120°C for 2 hours. Then add the laser cladding powder into the barrel of the coaxial powder feeding laser cladding equipment.

[0172] Step 2: Pre-treatment of the paper roller:

[0173] The paper roller to be repaired is pre-treated, and the failure and oxidation layers of the part to be repaired are removed by lathe, and then the rust, oil stains and impurities of the part to be repaired are removed. Among them, the rust can be removed by chemical cleaning with weak acid solution, and the oil stains can be removed by wiping with alcohol. Finally, the treated paper roller is clamped on the bed with a clamp.

[0174] Step 3: Preparation of paper roller cladding layer:

[0175] The ultra-high-speed laser cladding technology was used to repair the key parts of the paper roller surface by coaxial powder feeding. The specific cladding process parameters were: laser power of 3700W, spot diameter of 3mm, powder feeding rate of 42g / min, scanning speed of 25m / min, overlap rate of 75%, cladding layer thickness of 1mm, and protective gas flow rate of 9L / min. In the cladding process, the laser cladding area was protected by inert gas.

[0176] Step 4: Post-processing of the paper roller cladding layer:

[0177] (1) Allow the clad paper roller to cool to room temperature, then grind it to the required size on the drawing.

[0178] (2) Processing mesh patterns on the coating surface, with a transverse angle of 45°, to increase the longitudinal friction of the paper rolling roller surface, meeting the assembly and use requirements of the paper rolling roller.

[0179] (3) Finally, make correction for the runout. The runout of the paper rolling roller should not exceed 0.02A.

[0180] In the above-mentioned step c, the thickness of the cladding layer is 0.2 to 1 mm.

[0181] The inert gas in the above step c is argon.

[0182] The subsequent processing in the above step d includes post-machining of the parts whose size or surface accuracy of the workpiece does not meet the design requirements.

[0183] Evaluation of the effect of the invention:

[0184] (1) Coating Vickers hardness test

[0185] The Vickers hardness of the coating was measured by a HV-1000 digital Vickers hardness tester, with the experimental scale selected as HV0.2, a diamond pyramid indenter, and a loading time of 5 s.

[0186] (2) Coating friction and wear test

[0187] The friction and wear test was conducted on the coating layer prepared in Comparative Example 1 and Example 1 and 42CrMo steel using an SRV-4 wear tester. The test adopted a reciprocating motion form of ball-disc contact, and the friction pair was a GCr15 steel ball with a diameter of 10 mm. The test load was 20 N, the frequency was 10 Hz, the reciprocating stroke was 1 mm, the test time was 1 hour, and the temperature was room temperature. After the wear test, the volume of the worn part was measured using a laser confocal microscope.

[0188] (3) Coating corrosion, friction and wear test

[0189] The corrosion and wear test was conducted by using the MS-M9000 multifunctional wear tester to conduct reciprocating sliding friction tests on the samples. The corrosive liquid was a 3.5% NaCl solution. In order to avoid the potential interference and galvanic corrosion caused by the contact of dissimilar metals during the test, a Si3N4 ceramic ball with a diameter of 6mm was selected as the upper friction pair. The reciprocating frequency was 2Hz, the reciprocating sliding stroke was 5mm, the applied load was 20N, the test time was 3 hours, and the temperature was room temperature. After the wear test, the volume of the worn part was measured using a laser confocal microscope.

[0190] See Table 1, which is a comparison of the hardness of the coatings and 42CrMo steel substrates prepared in Comparative Example 1 and Example 1 of the present invention.

[0191] Table 1

[0192]

[0193] Table 1 is a comparison of the hardness of the coating of comparative example 1, embodiment 1 and 42CrMo steel substrate. It can be seen that the average hardness of the coating of comparative example 1 is 241.02HV, and the average hardness of the coating of embodiment 1 is 476.76HV, which are significantly improved compared with the microhardness of the substrate material 42CrMo steel. Moreover, by adjusting the element ratio, adding Mo element can further improve the hardness of the high entropy alloy coating (coating of embodiment 1). It is generally believed that the hardness value is one of the key indicators for measuring the wear resistance of the cladding coating.

[0194] See Table 2, which is a comparison of the wear volumes of the coatings prepared in Comparative Example 1 and Example 1 of the present invention and the 42CrMo steel substrate under dry friction conditions.

[0195] Table 2

[0196] Test subjects <![CDATA[Wear volume (×10 6 μm 3 )]]> Comparative Example 1 Coating 15.32±0.46 Example 1 Coating 4.48±0.57 42CrMo Steel 18.47±0.38

[0197] The wear volumes of the two coatings obtained in Comparative Example 1 and Example 1 and the substrate material 42CrMo steel were measured using a laser confocal microscope, as shown in Table 2.

[0198] As can be seen from Table 2, the wear volume of the coating of Example 1 is significantly smaller than that of the base material 42CrMo steel and the coating of Comparative Example 1, and the wear volume is reduced by 82.4%, indicating that the coating of Example 1 has a better wear resistance.

[0199] See Table 3, which is a comparison of the wear volumes of the coatings prepared in Comparative Example 1 and Example 1 of the present invention and the 42CrMo steel substrate under saline conditions.

[0200] Table 3

[0201] Test subjects <![CDATA[Wear volume (×10 6 μm 3 )]]> Comparative Example 1 Coating 18.84±0.52 Example 1 Coating 4.63±0.34 42CrMo Steel 26.28±0.56

[0202] The corrosion and wear volumes of the two coatings obtained in Comparative Example 1 and Example 1 and the substrate material 42CrMo steel under salt water conditions were measured using a laser confocal microscope. The results are shown in Table 3.

[0203] It can be seen from Table 3 that the wear volume of the coating in Example 1 is the smallest, which indicates that the addition of the Mo element enables the coating to have excellent corrosion resistance and wear resistance, and the wear resistance effect is optimal.

[0204] See also Figure 1 , Figure 1 This is the morphology of the CoCrFeNiMo high entropy alloy cladding powder prepared by the present invention.

[0205] See also Figure 2 , Figure 2 EDS of CoCrFeNiMo high entropy alloy cladding powder prepared by the present invention.

[0206] See also Figure 3 , Figure 3 The cross-sectional morphology of the coating prepared in comparative example 1 and example 1 of the present invention. Among them, 1 is the cross-sectional morphology of the coating prepared in comparative example 1, and 2 is the cross-sectional morphology of the coating prepared in example 1.

[0207] Depend on Figure 3 It can be seen that both groups of coatings are uniform and continuous, without defects such as macro cracks and pores.

[0208] See also Figure 4 , Figure 4 This is a real picture of the preparation of the wear-resistant layer of the paper milling roller prepared by the present invention. Among them, 1 is the pre-treatment of the paper milling roller, 2 is the coating cladding of the paper milling roller, and 3 is the post-processing of the paper milling roller.

[0209] The above is a detailed introduction to a paper milling roller repaired with a high entropy alloy material and an ultra-high-speed laser cladding method provided by the present invention. In this article, specific examples are used to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method and its core ideas of the present invention, including the best mode, and also enables any technician in the field to practice the present invention, including manufacturing and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in a number of ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements that are not different from the text of the claims, or if they include equivalent structural elements that are not substantially different from the text of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. Application of CoCrFeNiMo high entropy alloy in repairing paper rolling rollers and / or paper rolling roller coatings; The CoCrFeNiMo high entropy alloy, measured by element mass content, comprises: Co: 20.81% to 22.81%, Cr: 17.51% to 19.51%, Fe: 20.01% to 23.01%, Ni: 18.90% to 21.90% and Mo: 12.76% to 15.76%.

2. The use according to claim 1, characterized in that: The application method includes applying by ultra-high-speed laser cladding method; The CoCrFeNiMo high entropy alloy is specifically CoCrFeNiMo spherical powder; The material of the paper rolling roller includes CrMo steel.

3. The use according to claim 2, characterized in that: The CoCrFeNiMo spherical powder is obtained by spraying and granulating a CoCrFeNiMo slurry comprising a CoCrFeNiMo high entropy alloy powder, a dispersion medium and a binder; The particle size of the CoCrFeNiMo spherical powder is 30 to 50 μm; The application includes the application in improving the wear resistance and / or corrosion resistance of paper mill rollers.

4. The use according to claim 2, characterized in that: The thickness of the coating is 0.2 to 1 mm; In the CoCrFeNiMo slurry, the content of the binder is 0.6wt% to 0.8wt%; In the CoCrFeNiMo slurry, the content of the dispersion medium is 49.2wt% to 49.4wt%.

5. A paper milling roller or a repaired paper milling roller, characterized in that: It includes a paper rolling roller and a coating compounded on the paper rolling roller; The coating is a CoCrFeNiMo high entropy alloy coating; The CoCrFeNiMo high entropy alloy, measured by element mass content, comprises: Co: 20.81% to 22.81%, Cr: 17.51% to 19.51%, Fe: 20.01% to 23.01%, Ni: 18.90% to 21.90% and Mo: 12.76% to 15.76%.

6. A method for preparing or repairing a paper milling roller, characterized in that: The following steps are involved: 1) mixing CoCrFeNiMo high entropy alloy powder, a dispersion medium and a binder to obtain a CoCrFeNiMo slurry; The CoCrFeNiMo high entropy alloy, measured by element mass content, comprises: Co: 20.81% to 22.81%, Cr: 17.51% to 19.51%, Fe: 20.01% to 23.01%, Ni: 18.90% to 21.90% and Mo: 12.76% to 15.76%; 2) The CoCrFeNiMo slurry obtained in the above step is subjected to spray granulation and sintering to obtain CoCrFeNiMo spherical powder; 3) Under a protective atmosphere, the CoCrFeNiMo spherical powder obtained in the above steps is subjected to an ultra-high-speed laser cladding process to form a cladding layer on the to-be-repaired part of the paper rolling roller or on the paper rolling roller to be repaired, and then cooled to obtain a paper rolling roller composited with a CoCrFeNiMo high-entropy alloy coating or a repaired paper rolling roller composited with a CoCrFeNiMo high-entropy alloy coating.

7. The preparation method or repair method according to claim 6, characterized in that: The particle size of the CoCrFeNiMo high entropy alloy powder is 45 to 100 μm; The dispersion medium includes water; The binder includes polyethylene; In the CoCrFeNiMo slurry, the content of the binder is 0.6wt% to 0.8wt%; In the CoCrFeNiMo slurry, the content of the dispersion medium is 49.2wt% to 49.4wt%; The solid content of the CoCrFeNiMo slurry is 50% to 65%.

8. The preparation method or repair method according to claim 6, characterized in that: The mixing method includes grinding and mixing; The air inlet temperature of the spray granulation is 280-320°C; The outlet temperature of the spray granulation is 70-90°C; The sintering temperature is 800-1100°C; The particle size of the CoCrFeNiMo spherical powder is 30-50 μm.

9. The preparation method or repair method according to claim 6, characterized in that: The ultra-high-speed laser cladding process specifically comprises the following steps: ultra-high-speed laser cladding is performed by coaxial powder feeding; The laser power of the ultra-high-speed laser cladding process is 3500-3700W; The spot diameter of the ultra-high-speed laser cladding process is 2 to 3 mm; The powder feeding rate of the ultra-high-speed laser cladding process is 34-45 g / min.

10. The preparation method or repair method according to claim 6, characterized in that: The scanning speed of the ultra-high-speed laser cladding process is 20 to 30 m / min; The overlap rate of the ultra-high-speed laser cladding process is 70% to 85%; The shielding gas flow rate of the ultra-high-speed laser cladding process is 9 to 14 L / min; The cooling step also includes a machining step; The CoCrFeNiMo high entropy alloy coating includes a CoCrFeNiMo high entropy alloy coating with a textured structure.